IDENTIFIKASI KARAKTERISTIK POLA SPASIAL HULU HILIR PADI ORGANIK DI KABUPATEN SERDANG BEDAGAI - Annajmi, Nabila; Tjahjono, Boedi; Anwar, Syaiful (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Organic agriculture must be applied in an integrated manner, from upstream to downstream, forming a system. This subsystem is part of the market-oriented agribusiness concept by paying attention to quantity, quality, and continuity to gain income and agricultural productivity profits. This study aimed to look at the development of organic rice farming in the Serdang Bedagai Regency from a regional (spatial), agribusiness, and economic point of view. ANN analysis involves distance variables between agribusiness subsystems, road infrastructure, and transportation. The results of the analysis showed that the spatial pattern of organic rice formed in the Serdang Bedagai Regency was distributed, especially in Lubuk Bayas Village and Tanah Merah Village, with each having a value of R = 2.81 (R> 1) and R = 6.15 (R>1). Pematang Setrak Village had a clustered spatial pattern or had a value of R = 0.12 (R<1). This shows that the closer the locations between the subsystems are, the more profitable it is, thus saving production and transportation costs. The gains obtained were strengthened by the results of the R/C ratio produced, namely Tanah Merah Village with a value of 1.36, Lubuk Bayas Village with a value of 1.39, and Pematang Setrak Village with a value of 1.48. This means that farming activities are pretty efficient.